Srimpi Gadhěg Putri: a traditional dance of Pakualaman in The Langěn Wibawa’s manuscript - Febriyanto, Muhammad Bagus; Pudjiastuti, Titik (Institute of the Malay World and Civilization, Universiti Kebangsaan Malaysia, 2020)
Langěn Wibawa manuscript (thereafter abbreviated LW) with collection code of LL 20, belonging to the collection of Pura Pakualaman Yogyakarta Library, is a performing art-genre manuscript. This manuscript documents 28 dances in Kadipaten Pakualaman during Paku Alam IV reign. One of dances documented in LW manuscript is Srimpi Gadhěg Putri. Post-Paku IV reign, the Srimpi Gadhěg Putri was no longer recognized for its repertoire presentation. The disconnected preservation of Srimpi Gadhěg Putri dance whips the spirit to restudy the dance’s construction. By means of LW text, information on dance is dug and studied in order to be known by the public. Primary data of Javanese-language and letter manuscript was obtained using philological method yielding LW text edition. The next method, ethnochoreology, was used to study the component of Srimpi Gadhěg Putri dance including theme, music, dance arena, tata lampah dan tata rakit, and fashion and property. Considering the result of analysis, it can be seen that Srimpi Gadhěg Putri dance holds on standard rule of srimpi dance called lampah bědhayan, and refers to Kasultanan Ngayogyakarta dance tradition. Although following the rule of Srimpi dance in general, Srimpi Gadhěg Putri dance has such characteristics as kapang-kapang majěng procession in two stages, kaci fashion for the character of jaja and kandha narrative sang.